The Effect of Providing Nutritional Counseling on the Level of Knowledge, Attitudes, and Compliance with Fe Tablets Consumption for Pregnant Women with Anemia in the Grogol Community Health Center Area - Suryaningrum, Aprilia; Firmansyah; Rakhma, Luluk Ria; Soviana, Elida (Universitas Airlangga, 2024)
Background: Anemia contributes to maternal mortality during pregnancy, with a 2021 prevalence of 5.02% in Grogol. Non-compliance with Fe tablet consumption is a key factor. Nutritional counseling can effectively improve mothers' knowledge, attitudes, and compliance with Fe tablet intake. Objective: This study examines the impact of nutritional counseling on knowledge, attitudes, and compliance with Fe tablet consumption among anemic pregnant women at Grogol Community Health Center. Method: Using a pre-experimental one-group pre-post-test design, 35 anemic pregnant women in their second and third trimesters were randomly sampled from clinic records. They received 15-20 minutes of counseling with leaflets. Knowledge and attitudes were assessed via interviews and questionnaires, while compliance was measured using the pill count formula. The Wilcoxon Signed Rank Test evaluated changes from baseline to post-counseling. Results: Nutritional counseling increased knowledge (28.60%), attitudes (17.10%), and compliance (22.80%). Significant improvements were found in knowledge (p=0.001), attitude (p=0.001), and Fe tablet compliance (p=0.002). Conclusion: Nutritional counseling at the Grogol Community Health Center should be provided periodically to carry out promotive and preventive functions in the incidence of anemia in pregnant women.